Potensi Ekstrak Jagung Sebagai Pencegahan Katarak - Sri Mariati; Danang Diasrullah Bhekti; Alfa Sylvestris; Risma Karlina Prabawati (Puslitbang Sinergis Asa Professional, 2022)
Senile cataract is a cataract caused by the aging process that begins at the age of more than 50 years caused by free radicals, such as reactive oxygen species (ROS), formed as a result of external and internal exposure. Utilization of the potential of this corn extract has advantages with minimal side effects by utilizing corn extract, namely lutein zeaxanthin as a prevention of senile cataract. The main purpose of this literature review is to determine the potential of corn extract (Zea mays sp.) on the prevention of senile cataract. This research is literature study using national and international journals with the Scopus index published in 2016-2021 as well as literature books. Journals were obtained from search engines Google Scholar and Pubmed NCBI. Data and information obtained to support the research objectives. Cataracts are caused by Reactive Oxidative Stress (ROS). Zeaxanthin compounds work with their antioxidant properties by activating the synthesis of glutathione (GSH) in human RPE cells. Zeaxanthin increases the translocation of Nuclear receptor factor 2(Nrf2) by reducing the binding activity of Nrf2 to Kelch like ECH-Aasosiated protein 1 (Keapl1) in ARPE-19 cells. Furthermore, inhibition of GSH synthesis by buthionine suphoximine abolished the protective effect of zeaxanthin against oxidative stress-induced reduction of mitochondrial membrane potential and cell apoptosis in ARPE-19 cells thereby helping to prevent the formation of oxidative stress causing senile cataract. Corn extract (Zea mays sp.) has potential in the prevention of senile cataract because it has good antioxidant activity